2022
DOI: 10.1177/14747049221081733
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Emergent Leaders’ Faces and Evolution of Social Cheating: Cross-Cultural Experiments

Abstract: The aim of the present study was to investigate whether neutral faces of individuals with different propensities for leadership may convey information about their personal qualities, and are there impacts of sex, population and social environment on the facial perception. This study is based on a previous experiment ( Rostovtseva et al., 2022 ), where emergent leadership in the context of male group cooperation was investigated in Buryats (Mongolian population of Siberia). In the previous study three behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 102 publications
2
4
0
Order By: Relevance
“…The Tuvans did not evaluate facial emotional expressions between European and Mongolian faces differently (there was no lack of recognition of emotions on European faces). Similar conclusions were drawn in one of the previous studies, where no differences in the perception of facial features of Buryats (Mongolian people of Southern Siberia) were found between Caucasian and Mongolian raters (Russians and Buryats; Rostovtseva et al, 2022 ). We believe that these results can be explained by the impact of global international media (Internet, television, and cinema), which provides an opportunity for audiences from different parts of the world to become acquainted with different types of human appearances.…”
Section: Discussionsupporting
confidence: 91%
“…The Tuvans did not evaluate facial emotional expressions between European and Mongolian faces differently (there was no lack of recognition of emotions on European faces). Similar conclusions were drawn in one of the previous studies, where no differences in the perception of facial features of Buryats (Mongolian people of Southern Siberia) were found between Caucasian and Mongolian raters (Russians and Buryats; Rostovtseva et al, 2022 ). We believe that these results can be explained by the impact of global international media (Internet, television, and cinema), which provides an opportunity for audiences from different parts of the world to become acquainted with different types of human appearances.…”
Section: Discussionsupporting
confidence: 91%
“…Frontiers in Psychology frontiersin.org Similar conclusions were drawn in one of the previous studies, where no differences in the perception of facial features of Buryats (Mongolian people of Southern Siberia) were found between Caucasian and Mongolian raters (Russians and Buryats; Rostovtseva et al, 2022). We believe that these results can be explained by the impact of global international media (Internet, television, and cinema), which provides an opportunity for audiences from different parts of the world to become acquainted with different types of human appearances.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study (based on the same variant of the Trust Game as used in our study) also showed that people are unable to detect the trustworthiness of strangers through their facial appearance ( Jaeger et al, 2022 ). One of the possible reasons for the lack of actual recognition may be rooted in the so-called prosocial mimicry (or “camouflage”; Dawkins, 1976 ; Gambetta, 2005 ; Mokkonen and Lindstedt, 2016 ) used by free-riders (or cheaters) to imitate behavior and even appearance of prosocial individuals ( Rostovtseva et al, 2022a , b ). Although a fraction of such “cheaters” among trustworthy-looking individuals may be small, this still can introduce noise to the data.…”
Section: Discussionmentioning
confidence: 99%
“…Entering new social environments and interacting with strangers (which is especially common under modern urban conditions of big cities), most people do not trust indiscriminately: under such conditions, they use all kinds of information that may indicate the trustworthiness of their interaction partners. Several studies have shown that some individuals elicit more trust than others, even if the trusting person has never interacted with these individuals before ( Wilson and Eckel, 2006 ; Rezlescu et al, 2012 ; Brustkern et al, 2021 ; Rostovtseva et al, 2022a ). Apparently, humans use subtle cues to judge whether an interaction partner is trustworthy or not.…”
Section: Introductionmentioning
confidence: 99%